29.3: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex3 29.3#Ex3] || [[Item:Q8602|<math>\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex3 29.3#Ex3] || <math qid="Q8602">\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex4 29.3#Ex4] || [[Item:Q8603|<math>\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex4 29.3#Ex4] || <math qid="Q8603">\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex5 29.3#Ex5] || [[Item:Q8605|<math>\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex5 29.3#Ex5] || <math qid="Q8605">\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex6 29.3#Ex6] || [[Item:Q8606|<math>\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex6 29.3#Ex6] || <math qid="Q8606">\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex7 29.3#Ex7] || [[Item:Q8607|<math>\alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">alpha[p] = (1)/(2)*(nu - 2*p - 3)*(nu + 2*p + 4)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 3)*(\[Nu]+ 2*p + 4)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex7 29.3#Ex7] || <math qid="Q8607">\alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">alpha[p] = (1)/(2)*(nu - 2*p - 3)*(nu + 2*p + 4)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 3)*(\[Nu]+ 2*p + 4)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex8 29.3#Ex8] || [[Item:Q8608|<math>\beta_{p} = (2p+2)^{2}(2-k^{2})</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\beta_{p} = (2p+2)^{2}(2-k^{2})</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">beta[p] = (2*p + 2)^(2)*(2 - (k)^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Beta], p] == (2*p + 2)^(2)*(2 - (k)^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex8 29.3#Ex8] || <math qid="Q8608">\beta_{p} = (2p+2)^{2}(2-k^{2})</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\beta_{p} = (2p+2)^{2}(2-k^{2})</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">beta[p] = (2*p + 2)^(2)*(2 - (k)^(2))</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[\[Beta], p] == (2*p + 2)^(2)*(2 - (k)^(2))</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/29.3#Ex9 29.3#Ex9] || [[Item:Q8609|<math>\gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p)*(nu + 2*p + 1)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p)*(\[Nu]+ 2*p + 1)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/29.3#Ex9 29.3#Ex9] || <math qid="Q8609">\gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p)*(nu + 2*p + 1)*(k)^(2)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p)*(\[Nu]+ 2*p + 1)*(k)^(2)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|}
|}
</div>
</div>

Latest revision as of 12:09, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
29.3#Ex3 α p = 1 2 ( ν - 2 p - 2 ) ( ν + 2 p + 3 ) k 2 subscript 𝛼 𝑝 1 2 𝜈 2 𝑝 2 𝜈 2 𝑝 3 superscript 𝑘 2 {\displaystyle{\displaystyle\alpha_{p}=\tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}}}
\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}

alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex4 γ p = 1 2 ( ν - 2 p + 1 ) ( ν + 2 p ) k 2 subscript 𝛾 𝑝 1 2 𝜈 2 𝑝 1 𝜈 2 𝑝 superscript 𝑘 2 {\displaystyle{\displaystyle\gamma_{p}=\tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}}}
\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}

((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex5 α p = 1 2 ( ν - 2 p - 2 ) ( ν + 2 p + 3 ) k 2 subscript 𝛼 𝑝 1 2 𝜈 2 𝑝 2 𝜈 2 𝑝 3 superscript 𝑘 2 {\displaystyle{\displaystyle\alpha_{p}=\tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}}}
\alpha_{p} = \tfrac{1}{2}(\nu-2p-2)(\nu+2p+3)k^{2}

alpha[p] = (1)/(2)*(nu - 2*p - 2)*(nu + 2*p + 3)*(k)^(2)
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 2)*(\[Nu]+ 2*p + 3)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex6 γ p = 1 2 ( ν - 2 p + 1 ) ( ν + 2 p ) k 2 subscript 𝛾 𝑝 1 2 𝜈 2 𝑝 1 𝜈 2 𝑝 superscript 𝑘 2 {\displaystyle{\displaystyle\gamma_{p}=\tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}}}
\gamma_{p} = \tfrac{1}{2}(\nu-2p+1)(\nu+2p)k^{2}

((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p + 1)*(nu + 2*p)*(k)^(2)
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p + 1)*(\[Nu]+ 2*p)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex7 α p = 1 2 ( ν - 2 p - 3 ) ( ν + 2 p + 4 ) k 2 subscript 𝛼 𝑝 1 2 𝜈 2 𝑝 3 𝜈 2 𝑝 4 superscript 𝑘 2 {\displaystyle{\displaystyle\alpha_{p}=\tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}}}
\alpha_{p} = \tfrac{1}{2}(\nu-2p-3)(\nu+2p+4)k^{2}

alpha[p] = (1)/(2)*(nu - 2*p - 3)*(nu + 2*p + 4)*(k)^(2)
Subscript[\[Alpha], p] == Divide[1,2]*(\[Nu]- 2*p - 3)*(\[Nu]+ 2*p + 4)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex8 β p = ( 2 p + 2 ) 2 ( 2 - k 2 ) subscript 𝛽 𝑝 superscript 2 𝑝 2 2 2 superscript 𝑘 2 {\displaystyle{\displaystyle\beta_{p}=(2p+2)^{2}(2-k^{2})}}
\beta_{p} = (2p+2)^{2}(2-k^{2})

beta[p] = (2*p + 2)^(2)*(2 - (k)^(2))
Subscript[\[Beta], p] == (2*p + 2)^(2)*(2 - (k)^(2))
Skipped - no semantic math Skipped - no semantic math - -
29.3#Ex9 γ p = 1 2 ( ν - 2 p ) ( ν + 2 p + 1 ) k 2 subscript 𝛾 𝑝 1 2 𝜈 2 𝑝 𝜈 2 𝑝 1 superscript 𝑘 2 {\displaystyle{\displaystyle\gamma_{p}=\tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}}}
\gamma_{p} = \tfrac{1}{2}(\nu-2p)(\nu+2p+1)k^{2}

((1)/(2)*(nu - 2*p + 2)*(nu + 2*p - 1)*(k)^(2)) = (1)/(2)*(nu - 2*p)*(nu + 2*p + 1)*(k)^(2)
(Divide[1,2]*(\[Nu]- 2*p + 2)*(\[Nu]+ 2*p - 1)*(k)^(2)) == Divide[1,2]*(\[Nu]- 2*p)*(\[Nu]+ 2*p + 1)*(k)^(2)
Skipped - no semantic math Skipped - no semantic math - -